Consolidating democracy through integrating the chieftainship institution with elected councils in Lesotho: a case study of four community councils in Maseru - Kapa, Motlamelle Anthony (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2010)
This study analyses the relationship between the chieftainship institution and the elected councils in Lesotho. Based on a qualitative case study method the study seeks to understand this relationship in four selected councils in the Maseru district and how this can be nurtured to achieve a consolidated democracy. Contrary to modernists"Ÿ arguments (that indigenous African political institutions, of which the chieftainship is part, are incompatible with liberal democracy since they are, inter alia, hereditary, they compete with their elective counterparts for political power, they threaten the democratic consolidation process, and they are irrelevant to democratising African systems), this study finds that these arguments are misplaced. Instead, chieftainship is not incompatible with liberal democracy per se. It supports the democratisation process (if the governing parties pursue friendly and accommodative policies to it) but uses its political agency in reaction to the policies of ruling parties to protect its survival interests, whether or not this undermines democratic consolidation process. The chieftainship has also acted to defend democracy when the governing party abuses its political power to undermine democratic rule. It performs important functions in the country. Thus, it is still viewed by the country"Ÿs political leadership, academics, civil society, and councillors as legitimate and highly relevant to the Lesotho"Ÿs contemporary political system. Because of the inadequacies of the government policies and the ambiguous chieftainship-councils integration model, which tend to marginalise the chieftainship and threaten its survival, its relationship with the councils was initially characterised by conflict. However, this relationship has improved, due to the innovative actions taken not by the central government, but by the individual Councils and chiefs themselves, thus increasing the prospects for democratic consolidation. I argue for and recommend the adoption in Lesotho of appropriate variants of the mixed government model to integrate the chieftainship with the elected councils, based on the re-contextualised and re-territorialised conception and practice of democracy, which eschews its universalistic EuroAmerican version adopted by the LCD government, but recognises and preserves the chieftainship as an integral part of the Basotho society, the embodiment of its culture, history, national identity and nationhood.
Keywords: Customary law -- Lesotho; Constitutional law -- Lesotho; Local government -- Lesotho -- Maseru; Culture and law -- Lesotho -- Maseru; Lesotho -- Politics and government; Democracy -- Lesotho